National report on traineeships : Germany - Wolfgarten, Tobias [Verfasser]; Linten, Markus [Verfasser] (My University, 2012)
"Traineeships play a very important role in ensuring a smooth transition both between school and professional training or university and between graduation from university or training and employment. They offer an essential opportunity for young people to acquire practical skills that prepare them for their professional career." This contribution focuses on the situation concerning traineeships in Germany, considering the following aspects in particular: Traineeships as part of Member State's Youth Policy Measures; Legislative Framework for Traineeships; Availability of and Access to Traineeships; Practices and Content of Traineeships; Trainee's Rights and Terms and Conditions; Quality Assurance of Traineeships; Overall Assessment as regards Traineeships. (BIBB-Doku)
Keywords: S 1.6.1 Praktika; G 1.3.2.2 Übergänge; I 2.1 Deutschland; Praktikum; Berufsvorbereitung; Berufseinmündung; Bundesrepublik Deutschland